THE DECREASE IN THE LEVEL OF CORROSION HAZARD IN THE RATIONAL DESIGN OF METAL STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2023)
Expansion  of  functional  possibilities  of  the  use  of  combined  designs  in  the construction, improvement of architectural expressiveness of buildings and structures determine the need  for  improved  requirements  to  ensure  the  quality  and  reliability  of  means  and  methods  of corrosion protection. Currently, the development of computational methods to assess the reliability and  structural  safety  associated  with  the  construction  of  in-formation-analytical  database  key parameters of corrosion condition of metal construction. Methodology. This way creates the basis for  setting  and  implementing  management  tasks  operational  life  of  buildings  and  structures  in corrosive  environments  by  improving  the  quality  and  reliability  of  primary  and  secondary protection  of  steel  structures  based  on  the  level  of  corrosion  hazard.  Results.  When  using  the principles of the process approach is the formulation and implementation of tasks of management of operational  service  life  in  corrosive  environments.  The  principles  of  ensuring  safety  in  terms  of corrosion risk include the rationale for the sequence of steps to evaluate the survivability of building structures based on the principles of robust design, improvement and control measures the primary and secondary corrosion protection. Scientific novelty. The implementation of protection measures against  corrosion  according  to  the  corrosion  risk  criterion  helps  to  ensure  the  requirements  of reliability of building structures in accordance with the design provisions of limit state method and to solve the problems of control of technological security for the rated life of construction projects. objects.  Practical  significance.  The  proposed  generalized  indicators  of  the  actual  structures’ corrosion  state  determine  the  structure’s  operability  as  a  whole.  The  functional  dependencies between  the  operability  of  the  main  and  auxiliary  structures  are  established.  The  relationship between the values of corrosion resistance indicators and metal structures durability are determined. Actual technical condition control consists of checking that the values of these indicators are within acceptable limits. Taking into account the degree of operating environment aggressiveness is one of the determining factors in order to ensure the secondary protection effectiveness against corrosion. This procedure is the basis for the rational specifications appointment for anti-corrosion protection systems with subsequent display in the design and technological documentation.